Case of COVID-19 in a 5-week-old baby - Fleming, Rachael (BMJ Case Rep, 2020)
On 31 December 2019, the first case of COVID-19, was reported in Wuhan. A public health emergency of international concern was declared on 30 January 2020 and the first case in Scotland, on 2 March. The effect of COVID-19 appears to be less in the paediatric population and there are fewer cases reported in the literature in comparison to the adult population. Here, we report a case of a previously well 5-week-old infant who presented with fever and increased sleepiness. There was no known contact with any unwell individuals. COVID-19 was identified through a septic screen work up. The infant’s course was uneventful and she has made a full recovery. This case highlights the need to have a low index of suspicion in the diagnosis of COVID-19 and the need to be vigilant in use of personal protective equipment, even in paediatric patients with subtle symptoms.